Imagery and Figurative Language in Colleen Hoover’s Reminders of Him - Cahyadi, Aditya (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Language is a tool used by authors to organize their ideas in a literary work. This research aims to provide an explanation of the types of figures of speech and figurative language in the novel Reminders of Him by Coolleen Hoover. This research also describes the contribution of imagery and figurative language to romantic genre novels, which is researched using literary criticism methods and Abrams' theory of rhetoric. In this research, five types of imagery were found, namely visual imagery, auditory imagery, movement imagery, tactile imagery, and olfactory imagery. Apart from that, this research also found five types of figurative language, namely simile, metaphor, metonymy, synecdoche, and personification, used by Hoover in this novel. There were 406 types of imagery and 245 figurative languages found in this research. This study describes the use of imagery and figurative language in this novel. The use of imagery and figurative language here is used by the author as a tool in this work. The use of imagery and figurative language here helps to achieve special effects in the work, such as building an impression of the character, triggering the imagination, and providing an idea of the idea through the reader's sense of feeling. In line with this, the use of these two things also helps the author provide an explanation of his work, building the romantic nuance novel and also explains the role of imagery and figurative language in the intrinsic elements of this novel.